Exposure to Phenols, Phthalates, and Parabens and Development of Metabolic Syndrome Among Mexican Women in Midlife - Zamora, Astrid N.; Jansen, Erica C.; Tamayo-Ortiz, Marcela; Goodrich, Jaclyn M.; Sánchez, Brisa N.; Watkins, Deborah J.; Tamayo-Orozco, Juan Alfredo; Téllez-Rojo, Martha M.; Mercado-García, Adriana; Baylin, Ana; Meeker, John D.; Peterson, Karen E. (Frontiers in Public Health, 2021)
Evidence suggests exposure to endocrine-disrupting chemicals (EDCs) can influence Metabolic Syndrome (MetS) risk in adults, but it is unclear if EDCs impact women during midlife. We examined if EDCs measured in adult women were predictive of MetS and its components 9 years later. We measured urinary phthalate metabolites, phenols, and parabens collected in 2008 among 73 females from the ELEMENT study. MetS and its components (Abdominal Obesity, Hypertriglyceridemia, Cholesterolemia, Hypertension, and Hyperglycemia) were assessed in 2017. We regressed log-transformed EDC concentrations on MetS and MetS components using logistic regression, adjusting for age and physical activity. At follow-up, the mean (SD) age was 46.6 (6.3) years; the prevalence of MetS was 34.3%. ΣDBP, MBzP, and MEP were associated with an increased odds of hypertriglyceridemia. 2,5 DCP and 2,4 DCP were associated with increased odds of hypertriglyceridemia. The odds of hypertension were 4.18 (95% CI: 0.98, 17.7, p < 0.10) and 3.77 (95% CI: 0.76, 18.62, p < 0.10) times higher for every IQR increase in MCOP and Propyl Paraben, respectively. The odds of hyperglycemia were 0.46 (95% CI: 0.18, 1.17 p < 0.10) times lower for every IQR increase in ΣDEHP, and the odds of abdominal obesity were 0.70 (95% CI: 0.40, 1.21, p < 0.10) lower for every IQR increase in the concentration of triclosan. We found EDCs measured in 2008 were marginally predictive of hypertriglyceridemia and hypertension 9 years later. Results suggest that reductions in exposure to certain EDCs could improve metabolic risk markers among midlife women.